Adsorption of Pb(II) cation from aqueous solutions by acid modified low-rank coal An experimental study and simulation - Wang, Penghui (Water science and technology : a journal of the International Association on Water Pollution Research, 2021)
An acid modified approach to enhance the adsorption capacity of low-rank coal (lignite) is proposed to reduce the risk of heavy metal ions within the wastewater. Adsorption kinetics, adsorption thermodynamics, adsorption coefficient and density functional theory DFT calculations were studied in this paper, respectively. The results indicate that the adsorption capacity of lignite was enlarged after HNO3 modification, and pseudo-second order kinetics model and Langmuir isothermal adsorption model can be used to describe the adsorption process. The surface chemical properties of lignite play a dominant role rather than the specific surface area and total pore volume in the Pb(II) cation adsorption process, and it is suggested that the adsorption of Pb(II) cation by raw lignite (RL) and modified lignite (ML) is mainly completed by chemical adsorption. The Fourier transform infrared spectroscopy (FTIR) characterization showed that the surface oxygen functional groups of lignite increased after modification. The results of interaction energies between the model molecule and Pb(II) cation show that Pb(II) cation and -C-O-C are most easily combined, followed by -COOH, and -C = O is the weakest